Climate-adaptive water productivity: Building coherence across food, water, and land - CGIAR Initiative on National Policies and Strategies (CGIAR, 2023)
At the Cairo Water Week on October 31, 2023, the CGIAR Research Initiative on National Policies and Strategies (NPS) conducted a session focusing on the empirical analysis of Egypt’s climate-adaptive water productivity programmes. This session aims to highlight the multifaceted aspects of water productivity and emphasize the existing and best practices.